A REVIEW: PERFORMANCE MAPPING OF DESIGN–BID–BUILD AND DESIGN–BUILD IN GOVERNMENT PROJECTS BASED ON LEAN CONSTRUCTION - Endah Murtiana Sari; Slamet Imam Wahyudi; Henny Pratiwi Adi; Tezara Cionita (LPPM Universitas Negeri Jakarta, 2026)
Government projects have a significant impact on public welfare and economic development, particularly in developing countries such as Indonesia. Under the prevailing regulations, government project delivery systems are generally categorized into two types: Design–Bid–Build (DBB) and Design–Build (DB). Achieving and improving the performance of government projects is essential to ensure contractual compliance and to serve as a model of best practices and lessons learned. This study aims to analyze the factors influencing the performance of government projects under both DBB and DB systems through a comprehensive literature review of prior studies. By employing an exploratory qualitative approach, this research identifies key factors as the main variables that should be considered in measuring government project performance for both delivery methods. The findings can be used to develop a Government Project Performance model for DBB and DB systems by project stakeholders as well as by academics who intend to further refine and expand this model in future research.